PENERAPAN MEDIA PEMBELAJARAN BoneLab UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK - Siti Rabiatul Fajri; Titi Laily Hajiriah; Islahiyah Islahiyah (Bioscientist : Jurnal Ilmiah Biologi, 2020)
This study aims: 1) to find out the increase in student learning outcomes; and 2) to find out students' responses after applying BoneLab learning media in class VIII at MTs. Nahdlatul Mujahidin NW Jempong. The research method uses Classroom Action Research (CAR), which consists of 2 cycles, each cycle containing the stages of preparation, implementation, observation, and reflection. The research instruments consisted of: 1) teacher observation sheet activity; 2) student observation sheet activity; 3) learning achievement test sheets; and 4) student questionnaire response sheets. The data analysis technique used is quantitative descriptive analysis with percentages. The results of the study stated that, the activities of teachers in the first cycle carried out "very well" with an average percentage of 86.48%. Whereas in the second cycle, it performed "very well" with an average percentage of 89.60%, an increase of 3.12%. Activities of students in the first cycle, the average percentage obtained was 89.30% with the category "very good". While in cycle II, the average percentage obtained was 91.5% with the category of "very good", an increase of 2.2%. The percentage of the number of students experiencing mastery learning outcomes of students in the first cycle was 46%, and in the second cycle was 66%. The percentage of students' responses to learning is 82.8%.